2013
DOI: 10.1093/mutage/get040
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal mitotic spindle assembly and cytokinesis induced by D-Limonene in cultured mammalian cells

Abstract: d-Limonene is found widely in citrus and many other plant species; it is a major constituent of many essential oils and is used as a solvent for commercial purposes. With the discovery of its chemotherapeutic properties against cancer, it is important to investigate the biological effects of the exposure to d-Limonene and elucidate its, as yet unknown, mechanism of action. We reported here that d-Limonene is toxic in V79 Chinese hamster cells in a dose-dependent manner. Moreover, to determine the cellular targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The cytotoxicity of these EOs may be attributed to the limonene and citral (the case of Li.cu EO). These constituents are reported in the literature for their cytotoxic activity with Mauro and collaborators, showing the toxicity of limonene on V79 since it affected the dividing cells so preventing the assembly of mitotic spindle microtubules. Likewise, Ghosh pointed out the citral effect on the mitochondrial activity of cancer cells.…”
Section: Resultsmentioning
confidence: 56%
“…The cytotoxicity of these EOs may be attributed to the limonene and citral (the case of Li.cu EO). These constituents are reported in the literature for their cytotoxic activity with Mauro and collaborators, showing the toxicity of limonene on V79 since it affected the dividing cells so preventing the assembly of mitotic spindle microtubules. Likewise, Ghosh pointed out the citral effect on the mitochondrial activity of cancer cells.…”
Section: Resultsmentioning
confidence: 56%
“…Hence, antioxidants originating from plants are attracting attention (Suttirak and Manurakchinakorn, 2014;Stone et al, 2014) Some studies have demonstrated that orange peel oil can be used as a medical agent that protects against cancer and prevents the growth and proliferation of cancer cells by d-Limonene. The orange essential oil contains large quantities of d-Limonene is present, which has anti-proliferative and apoptosis-inducing effects (Mauro et al, 2013;Crowell and Gould, 1994). Thus, it is used as a chemopreventive and chemotherapeutic agent against multiple types of tumors (Vigushin et al, 1998;Chaudhary et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…d -Limonene, the most abundant constituent of navel orange essential oil, has been shown to have anti-proliferative and apoptosis-inducing effects [ 25 , 26 ], thus it has been used as a chemopreventive and chemotherapeutic agent against multiple types of tumors [ 27 , 28 ]. Other components of the essential oil, such as α-pinene, have been shown to inhibit growth of non-small-cell lung carcinoma cells [ 29 ].…”
Section: Resultsmentioning
confidence: 99%